(untitled) (The Review of Diabetic Studies, 2020)
AIM: The study aimed to investigate the possible relationship between diabetic peripheral neuropathy (DPN) and the development of depressive symptoms in patients with type 2 diabetes mellitus (T2D). METHODS: A comparative nonexperimental study was conducted. Ninety-five T2D individuals aged 65 years and more were recruited. The sample was divided into two groups: 50 participants with T2D and without DPN and 45 participants with T2D and DPN. The Patient Health Questionnaire 9 (PHQ-9) was used to collect information about low mood and depression symptoms in the subjects recruited. RESULTS: Participants with DPN recorded higher scores on PHQ-9 than those with T2D only. The mean PHQ-9 score for the DPN group (6.09) was significantly higher than that for the T2D only group (2.24) (p < 0.001). Participants with DPN were more likely to have mild to moderate or moderately severe low mood and depression symptoms than T2D only participants who exhibited minimal to no low mood and depressive symptoms. CONCLUSIONS: The association between DPN and depression is confirmed by this study, with significant depressive symptoms found in patients with neuropathy when compared to diabetes patients with no neurological complications. It is therefore important that discomfort and emotional problems caused by DPN should be taken seriously and addressed closely in the management of DPN in order to prevent depression. Also, a change in screening practices to identify patients with diabetes and depressive symptoms is required.